Peningkatan Respon Kebal Non-spesifik dan Pertumbuhan Ikan Nila (Oreochromis niloticus) Melalui Pemberian Jahe, Zingiber officinale - Payung, Clara Nunia; Manoppo, Henky (e-Journal BUDIDAYA PERAIRAN, 2015)
The purpose of this research was to evaluate the effect ginger supplemented in food on nonspecific immune response of nile tilapia.  Juveniles with an average of weight of 27.31 g were obtained from Fish Culture and Development Board  (BP3I) Tateli and then transported to Faculty of Fisheries and Marine Science.  Fish were then cultured in 15 aquaria with a density of 15 fish per aquarium. Each aquarium was equipped with an aerator and used water recirculation system to keep the water quality still in good condition. After adaption for one weeks, fish was fed pellet supplemented with  ginger powder as treatments at five different doses including A=0, B=2,5, C=5, D=7,5, and  E=10 g/kg, each with three replications.  Fish was fed as long as four weeks at 3%/bw/d, twice daily at 08.00 am and 17.00 pm.  Data consisting of total leucocyte count and phagocytosis activity of phagocyte cells were collected at two weeks interval. Research results showed that supplementation of ginger powder into fish pellet  had significant effect on the increase of nonspecific immune response. The highest total leucocyte count and phagocytosis activity of phagocyte cells was observed on fish fed pellet supplemented with 7.5 g/kg of food and significantly different as compared to those of control fish.  As conclusion, supplementation of ginger powder into fish pellet could increase nonspecific immune response on nile tilapia. Keywords: Ginger, nonspecific immune response, total leucocytes count, phagocytosis activity, nile tilapia